Higher Anxiety and Will to Live Are Associated With Poorer Adherence to Cardiac Rehabilitation. Issue 6 (November 2019) - Harris, Kristie M.; Anderson, Derek R.; Landers, Jacob D.; Emery, Charles F.
Abstract : Purpose: Cardiac rehabilitation (CR) session attendance and rates of completion remain suboptimal. Greater distress (ie, depression and anxiety) has been associated with both better and poorer adherence. Will to live (ie, desire, determination and effort to survive) has been associated with survival among cardiac patients and thus may be relevant for CR adherence. It was hypothesized that depression and anxiety would be negatively associated with adherence, and that will to live would moderate these relationships. Methods: Sixty patients (mean age = 56.9 ± 10.8 yr; 38 males) entering outpatient CR completed self-report measures of will to live (Wish to Prolong Life Questionnaire) and distress (Hospital Anxiety and Depression Scale). Hierarchical regression analyses were performed to predict CR session attendance (%) and program completion (yes/no) from depression and anxiety, as well as the interaction of those variables with will to live. Results: Neither depression nor anxiety was associated with CR adherence ( P s > .33). However, there was a significant interaction of will to live with anxiety in predicting attendance (β= −0.31, P = .03, Model R 2 = .19, P = .01), reflecting that anxiety predicted lower attendance only among patients reporting greater will to live. Conclusions: These data help clarify the complex relationship between distress and CR adherence. Findings suggest that higher anxiety is associated with poorer adherence, but only in combination with greater motivation for living. Patients higher in anxiety and will to live may benefit from additional strategies to make actionable behavioral change in the context of CR. Abstract : Will to live (ie, desire, determination, and effort to survive) moderated the relationship of anxiety with cardiac rehabilitation (CR) adherence. Findings suggest that higher anxiety is associated with poorer adherence, but only in combination with greater motivation for living. These data help clarify the complex relationship between distress and CR adherence.